Identification of promising chickpea interspecific derivatives for agro-morphological and major biotic traits - Singh, Mohar; Kumar, Tapan; Sood, Salej; Malhotra, Nikhil; Rani, Upasana; Singh, Sarvjeet; Singh, Inderjit; Bindra, Shayla; Kumar, Sanjeev; Kumar, Sandeep (Frontiers in Plant Science, 2022)
The wild Cicer species are well-known for having climate-resilient and productivity-enhancing traits of interest. Therefore, wide hybridization could be used as a realistic strategy for introgressing prospective traits from wild species into the cultivated gene pool. The present study was, thus, undertaken to evaluate F7 chickpea interspecific derivatives derived from Cicer reticulatum Ladiz. and C. echinospermum P. H. Davis wild annual Cicer species. As a result, a set of six interspecific crosses were advanced using single seed descent (SSD) method of breeding. The F7 generation of these crosses was assessed in two diverse agro-ecological regions of India. The data revealed a wide range of variation with respect to seed yield and its important component traits, which resulted into the identification of most promising derivatives carrying desirable characters as indicated by range, mean and coefficient of variation. Further, fruitful heterosis was also estimated as promising selection criteria for identifying superior lines for earliness and high seed yield including resistance against prevailing stresses (ascochyta blight, botrytis gray mold, dry root rot and fusarium wilt). The superior derivatives carrying putative characters could be recommended for further breeding and selection of genetic materials for developing suitable genotypes.